18 holes with Bing : golf, life, and lessons from Dad - Crosby, Nathaniel; Strege, John; Nicklaus, Jack (New York, NY : Dey St., an imprint of William Morrow Publishers, 2016)
In this love letter to his father, former professional golfer Nathaniel Crosby shares memories of Bing Crosby on the golf course, and the lessons he taught him about the game and about life. The beloved singer and star was also an extraordinary teacher who instilled an abiding passion and mastery of the game in his youngest son, Nathaniel. Winning the US Amateur at nineteen, Nathaniel went on to compete in high-level professional tournaments for his entire life. Nathaniel introduces us to the Bing Crosby he and his family knew-- not the beloved singer who played golf, but a golfer who sang to pay his country club dues. Nathaniel shares exclusive stories about this American icon golfing, working, and playing with some of the most famous people in history-- royalty, titans of industry, stars of stage and screen, and champions of the green, including Bob Hope, Dwight Eisenhower, Ben Hogan, Jack Nicklaus, and Louis Armstrong. At the book's heart is an intimate account of a father and a son-- how a mutual love of golf formed an exceptional emotional bond. Full of anecdotes, vignettes, and recollections of Bing's time on the course, the tournaments he created and later sponsored, and the constant encouragement he showed his son.
As famous as famous gets -- Grass roots -- The jazz singer -- The War years -- A British bond -- Caddies or kings -- Hogan and the incredible match -- Family friends -- Crosby and Hope : road to the gold course -- The Crosby clambake -- Pirates, pugilists, horses, and hunting -- On parenting -- Our time together -- The world mourns -- Growing up fast -- Winning for Dad -- Aftermath -- Dad's legacy.
Keywords: Crosby, Bing, -- 1903-1977; Crosby, Nathaniel; Golf -- Anecdotes